The Analysis of Household Economic Behavior of Clove Farmers in Ponggiha Village Lasusua District North Kolaka Regency - Husnaeni Husnaeni; Rosmawaty Rosmawaty; Munirwan Zani (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2022)
This study analyzes the economic behavior of clove farmer households in Ponggiha Village, Lasusua District, North Kolaka Regency. The household economy includes a discussion of the economic behavior of clove farmer households in terms of production, working time, and income. This research was conducted from September – November 2021. The population in this study were clove farmer households in Ponggiha Village. The research sample comprised 76 respondents from farmer households selected using the Slovin formula. The variables of this study were the characteristics of the respondents consisting of age, education, family dependents, and farmer status, as well as the characteristics of household economic behavior, which included the amount of production, working time, and income. The data analysis applied is the econometric model of multiple linear regression analysis. Based on the research that has been done, it is found that the level of clove farming production is influenced by land area with a contribution of 21.6%, production costs and working time of clove farming. The working time of non-clove farming significantly affects the working time of clove farming with a contribution of 49.5%. For the contribution of clove, farming household income is influenced by the amount of clove production with a contribution of 22%, and clove farming income is higher than non-clove farming income.